A meta-analysis of the association between preoperative magnetic resonance imaging and surgical outcomes in newly diagnosed breast cancer - Li-Li Xie; Zhi-Hong Xu; Deng-Hui Wei; Chun-Sen Xu (Archives of Medical Science)
Introduction The use of preoperative magnetic resonance imaging (MRI) in newly diagnosed breast cancer has been increasing. However, the value of MRI applied to women with newly diagnosed breast cancer remains controversial. Therefore, this study focused on the association between preoperative MRI and surgical outcomes, which include mastectomy rate, breast conservation rate, and re-excision rate.